Pengaruh Stabilitas Keuangan, Tekanan Eksternal dan Target Keuangan Terhadap Kecurangan Laporan Keuangan - Cindy Loren Panggabean; Juniati Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial stability, external pressure, and financial targets on financial statement fraud in companies operating in the consumer cyclicals subsector on the Indonesia Stock Exchange (IDX). Using data from consumer cyclicals companies listed on the IDX during the 2021-2024 period, this study tests the proposed hypotheses. Financial stability is measured by changes in assets, while external pressure is proxied using the leverage ratio. Financial targets are measured by Return on Assets. Data analysis was conducted using the classical assumption test to identify variables that significantly influence the probability of financial statement fraud. The results show that financial stability has a positive and significant effect on financial statement fraud, external pressure has no positive effect, and financial targets have no positive impact on financial statement fraud.